2021
DOI: 10.1002/ange.202017181
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Dynamic Chemical State of Catalysts with the Product Profile of Electrocatalytic CO2 Reduction

Abstract: USA). He joined the Department of Chemistry as an assistant professor at NTU in 2013 and was promoted to associate professor in 2018. His current research interests include the development of in situ/operandom ethodology for studying liquid/solid interfaces and the synthesis of nanomaterials for energy conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…Energy-efficient NO 3 RR points to low operating overpotentials (e.g., >−0.2 V vs. RHE), at which transition metal (e.g., Cu and Co)-based catalysts often suffer from potential−dependent phase evolution, leading to the coexistence of multiple phases, such as metallic, oxide and hydroxide phases 53 56 . In situ monitoring of the phase evolution of transition metals during the NO 3 RR, while correlating these intermediate phases with specific catalytic steps 53 , 54 , 57 , 58 , may not only guide the rational design of selective catalysts for NH 3 but also provide insight into the NO 3 RR. Inspired by the tandem NO 3 − -to-NH 3 conversion in nature 29 , we sought, therefore, to circumvent the scaling relations by combining two or more cooperative intermediate phases exhibiting complementary catalytic selectivity into one tandem system, intending to achieve NH 3 synthesis at low overpotentials.…”
Section: Introductionmentioning
confidence: 99%
“…Energy-efficient NO 3 RR points to low operating overpotentials (e.g., >−0.2 V vs. RHE), at which transition metal (e.g., Cu and Co)-based catalysts often suffer from potential−dependent phase evolution, leading to the coexistence of multiple phases, such as metallic, oxide and hydroxide phases 53 56 . In situ monitoring of the phase evolution of transition metals during the NO 3 RR, while correlating these intermediate phases with specific catalytic steps 53 , 54 , 57 , 58 , may not only guide the rational design of selective catalysts for NH 3 but also provide insight into the NO 3 RR. Inspired by the tandem NO 3 − -to-NH 3 conversion in nature 29 , we sought, therefore, to circumvent the scaling relations by combining two or more cooperative intermediate phases exhibiting complementary catalytic selectivity into one tandem system, intending to achieve NH 3 synthesis at low overpotentials.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al found that in situ generated CO 2 RR intermediates on the surface of OD-Cu stabilize Cu δ+ species 8 . Chen et al pointed out that the chemical states of Cu are associated with the oxidation caused by an uncertain oxidative species in the electrolytes 25 27 . We took the view that the Cu δ+ species should be dynamically existing, and we propose that the redox conditions provided by electrochemical cathodic reduction and oxidative species in electrolytes should be crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, researchers focus on the development of various catalysts with high activity. [9][10][11] Similarly, substantial efforts have been invested in the fabrication of different CRR catalysts, including single-atom, 12 alloy, 13,14 surface oxidation state, [15][16][17] grain boundaries, 18 solid solutions, 19 morphologies, 20,21 chemical composition, 22 and crystal facet engineering. 23 Nevertheless, differently to thermal catalysis, since CRR occurs on a gas/solid/liquid three-phase interface (Figure 1C), 24 its reactivity is also sensitive to the local reaction environment of the catalysts, such as the specific electrolyte, 25 pH, 26 presence of metal cations, 27 surface structure and composition of the catalyst, 28 and some other factors.…”
Section: Introductionmentioning
confidence: 99%